The risk of mortality among people with type 2 diabetes in Latin America: A systematic review and meta-analysis of population-based cohort studies - Carrillo-Larco, Rodrigo M. (2019)
Type 2 diabetes mellitus (T2DM) is associated with a high mortality risk, although the magnitude of this association remains unknown in Latin America (LA). We aimed to assess the strength of the association between T2DM and all-cause and cause-specific mortality in population-based cohort studies in LA. Systematic review and meta-analysis: inclusion criteria were (1) men and women 18 years old and above with T2DM; (2) study outcomes all-cause and/or cause-specific mortality; and (3) using people without T2DM as comparison group. Five databases (Scopus, Medline, Embase, Global Health, and LILACS) were searched. Risk of bias was evaluated with the ROBINS-I criteria. Initially, there were 979 identified studies, of which 17 were selected for qualitative synthesis; 14 were included in the meta-analysis (N = 416 821). Self-reported T2DM showed a pooled relative risk (RR) of 2.49 for all-causes mortality (I-squared [I 2 ] = 85.7%, p < 0.001; 95% confidence interval [CI], 1.96-3.15). T2DM based on a composite definition was associated with a 2.26-fold higher all-cause mortality (I 2 = 93.9%, p < 0.001; 95% CI, 1.36-3.74). The pooled risk estimates were similar between men and women, although higher at younger ages. The pooled RR for cardiovascular mortality was 2.76 (I 2 = 59.2%; p < 0.061; 95% CI, 1.99-3.82) and for renal mortality 15.85 (I 2 = 0.00%; p < 0.645; 95% CI, 9.82-25.57). Using available population-based cohort studies, this work has identified and estimated the strength of the association between T2DM and mortality in LA. The higher mortality risk compared with high-income countries deserves close attention from health policies makers and clinicians to improve diabetes care and control hence preventing complications and delaying death.